1994
DOI: 10.1002/jmv.1890440115
|View full text |Cite
|
Sign up to set email alerts
|

Detection of respiratory syncytial virus by RNA‐polymerase chain reaction and differentiation of subgroups with oligonucleotide probes

Abstract: The polymerase chain reaction (RNA-PCR) was used for specific detection of respiratory syncytial virus (RSV) genomes in clinical specimens. A set of primers was selected from conserved regions of the 1B and N genes for detection of both subgroups. The primers were found to be RSV specific, all RSV strains generated a 218 bp product, and no RSV specific amplified product was obtained when nucleic acids from a variety of micro-organisms from the respiratory tract were subjected to the RNA-PCR. We took advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…These findings are consistent with those of other studies previously reported, which have used monospecific or multiplex RT-PCR assays for the detection of viral infections (2,11,12,25). Although oligonucleotide hybridization confirms the specificity of the amplified PCR product, there is also evidence of improved sensitivity of PCR assays with oligonucleotide hybridization compared to the sensitivity of PCR assays with agarose gels for the detection of infection (10,28). RT-PCR-EHA incorporates both the RT-PCR technology and microplate hybridization for confirmation of results, with the combination of both techniques potentially augmenting the sensitivity of this assay.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those of other studies previously reported, which have used monospecific or multiplex RT-PCR assays for the detection of viral infections (2,11,12,25). Although oligonucleotide hybridization confirms the specificity of the amplified PCR product, there is also evidence of improved sensitivity of PCR assays with oligonucleotide hybridization compared to the sensitivity of PCR assays with agarose gels for the detection of infection (10,28). RT-PCR-EHA incorporates both the RT-PCR technology and microplate hybridization for confirmation of results, with the combination of both techniques potentially augmenting the sensitivity of this assay.…”
Section: Discussionmentioning
confidence: 99%
“…8 Another approach tested for the detection of non-US APVs includes the use of digoxigenin-labeled (F gene based) primers for PCR and then immunochemiluminescent Southern blotting of the PCR product. 8,25 This method has the advantage of increased sensitivity and also reduced risk of false-positive reactions. More recently, an M gene-based PCR assay has been described for the detection of APV-US infection.…”
Section: Discussionmentioning
confidence: 99%
“…The two hMPV RT-PCRs were integrated in the existing in-house RT-multiplex PCR as follows: primers for the hMPV N gene were combined with those for RSV, influenza viruses A and B (block 1), and primers for HMPV L gene were combined with those for adenoviruses and parainfluenza type 1 and type 3 viruses (block 2) [6,13,20,26,38]. RNA of RNA viruses was transcribed to cDNA before PCR was performed.…”
Section: Laboratory Investigationsmentioning
confidence: 99%